Analisis Kesuksesan Sistem E-Kinerja Pada Satuan Kerja Menggunakan Enhanced Information System Success Model - Dedi Suardika, I Made; I Made Candiasa; Dewa Gede Hendra Divayana (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
The implementation of the Electronic Performance System (E-Kinerja) in the working units in Denpasar City is a primary concern in efforts to enhance the efficiency and effectiveness of employee performance management. E-Kinerja is an obligatory electronic system based on a website that is used by civil servants in Denpasar City. During its implementation, the E-Kinerja system encounters several common issues such as server disruptions (server downtime), login errors, employee data inconsistencies, and employees' low understanding in operating the E-Kinerja system. This study aims to measure and analyze the level of success in implementing the E-Performance system using the Enhanced Information System Success Model, which is an improvement of the SI DeLone and McLean (2003) success model. The model incorporates five measurement variables: information quality, system quality, service quality, user satisfaction, and net benefits. This study employed the technique of proportional stratified random sampling with a sample size of 100 civil servants. The method of data collection involves distributing questionnaires to the government employees in the Denpasar area who are users of the E-Performance system. The obtained data was analyzed using the statistical method of Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of the SmartPLS 3.3 application. The hypothesis testing results reveal that the influence of information quality on user satisfaction is positively valued at 0.300. The impact of system quality on user satisfaction is positively valued at 0.288. The influence of service quality on user satisfaction is positively valued at 0.280. The influence of user satisfaction on user interest is positively valued at 0.824. Thus, it can be concluded that the influence of all research variables is significant and all hypotheses in this study can be accepted. This research is expected to serve as input and evaluation for policymakers regarding the factors that influence the success of the E-Performance system in Denpasar City, in order to enhance and develop the system sustainably. Additionally, it can also serve as a reference for future research in the field of information system success analysis.